Regulatory Mechanisms of L-Lactic Acid and Taste Substances in Chinese Acid Rice Soup (Rice-Acid) Fermented With a Lacticaseibacillus paracasei and Kluyveromyces marxianus - Liu, Na; Qin, Likang; Miao, Song (Frontiers in Microbiology, 2021)
Rice-acid has abundant taste substances and the health protection function due to its various bioactive compounds, such as organic acids. L-lactic acid is the most abundant organic acid in rice-acid, but the regulatory mechanisms of L-lactic acid accumulation in rice-acid are obscure. In the study, we analyzed the dynamic changes in organic acids and taste substances in rice-acid in various fermentation phases and different inoculation methods. We identified the key genes involved in taste substance biosynthesis by RNA-Seq analysis and compared the data of four experimental groups. We found that the differences in key functional genes (L-lactate dehydrogenase and D-lactate dehydrogenase) and key metabolism pathways (glycolysis, pyruvate metabolism, TCA cycle and amino acid biosynthesis and metabolism) might interpret the accumulation of L-lactic acid, other organic acids and taste substances in rice-acid fermented with Lacticaseibacillus paracasei. The experimental data provided the basis for exploring regulatory mechanisms of taste substance accumulation in rice-acid.